2022
DOI: 10.3390/molecules27031104
|View full text |Cite
|
Sign up to set email alerts
|

Soyauxinine, a New Indolopyridoquinazoline Alkaloid from the Stem Bark of Araliopsis soyauxii Engl. (Rutaceae)

Abstract: The chemical investigation of the total alkaloid extract (TAE) of the stem bark of Araliopsis soyauxii (Rutaceae) afforded an unreported indolopyridoquinazoline (compound 1) along with nine previously known alkaloids 2-10. In addition, six semi-synthetic derivatives 3a-c, 4b, 5a and 6a were prepared by allylation and acetonidation of soyauxinium nitrate (5), edulinine (3), ribalinine (4) and arborinine (6). The structures and spectroscopic data of five of them are reported herein for the first time. The sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Treatment of CCRF-CEM cells with the compound at 3.64 μM IC 50 altered mitochondrial membrane potential and elevated ROS levels and apoptotic caspase protein expression in the leukemia cells. However, according to Noulala et al [ 61 ], soyauxinine showed poor antiproliferative effects on colon HT-29 and prostate PC-3 cancer cells.…”
Section: Anticancer Alkaloids From Plantsmentioning
confidence: 99%
“…Treatment of CCRF-CEM cells with the compound at 3.64 μM IC 50 altered mitochondrial membrane potential and elevated ROS levels and apoptotic caspase protein expression in the leukemia cells. However, according to Noulala et al [ 61 ], soyauxinine showed poor antiproliferative effects on colon HT-29 and prostate PC-3 cancer cells.…”
Section: Anticancer Alkaloids From Plantsmentioning
confidence: 99%
“…As mentioned above, this tricyclic compound can inhibit HCV replication, but it is less potent than pseudane IX [ 21 ], and it contributes to the antifungal activity of the plant extract [ 19 ]. Arborinine can be isolated from diverse plants, including Rutaceae such as Vepris trichocarpa and Vepris teva [ 52 , 53 ], Araliopsis soyauxii [ 54 ] and different Ruta species [ 55 ]. Interestingly, the acridone alkaloid has been shown to exert marked antitumor activities.…”
Section: Bioactive Phytochemicals From R Angustifolia ...mentioning
confidence: 99%